Development of Digital-based Comic Media as an Innovative Learning Tool in the Literatur und Gesellschaft Course to Understand German Literature in the “Weimar Republic” Era - Faishal Ramadhan Firdausi; Dudy Syafruddin (Universitas Negeri Malang, 2025)
This article discusses the development of digital comics as innovative learning media for the Literature und Gesellschaft course in the German Language Education Study Program, State University of Malang, which is specifically aimed at helping students understand the context of German history and literature during the Weimar Republic. This development uses the 4D model (Define, Design, Develop, Disseminate), with a focus on creating and testing comics based on learning needs and input from expert validators. The validation process involved one material expert and one media expert, who concluded that the comic was suitable for use with minor revisions. The comic was rated “excellent” in terms of visual design and “good” in terms of content clarity and historical relevance. The comic uses visual narratives to simplify complex socio-historical content. Pilot test results showed a spike in student engagement, comprehension and enthusiasm for learning. This study concludes that digital comics on literature during the Weimar Republic are a promising alternative for learning German literary history, especially in presenting abstract material through a more understandable and accessible format.